Deepening the Conception of Functional Information in the Description of Zoonotic Infectious Diseases - Michael Kosoy (Entropy, 2013)
Infectious agents, their hosts, and relevant abiotic components are directly involved in the complex dynamic process of maintaining infectious diseases in Nature. The current tendency to focus on host-pathogen interactions at the molecular and organismal levels does not advance our knowledge about infectious diseases, as much as it potentially could, by ignoring the ecological context pivotal for understanding the biology of the diseases. A new model of investigation requires a dynamic shift of perspectives in the “simplicity-complexity” dimension: from virulence factors to multi-sided descriptions of the pathogens; from particular microbes to wide microbial communities; from clinical manifestations to a variety of infectious patterns; from findings of infectious agents to defining a natural focus of the infection as a self-regulated system; from single factors affecting host-parasite relations to the complex ecological context. Various aspects of interactions between hosts, vectors, pathogens, and environmental niches should be integrated at multiple spatiotemporal scales and at different levels of biological organization (molecular, genomic, organismal, population, and ecosystem).